Boundary Element Calculations for Normal Contact of Soft Materials With Tensed Surface Membrane - Yuan, Weike; Wang, Gangfeng (Frontiers in Mechanical Engineering, 2020)
This work considers the non-adhesive frictionless contact problem of soft materials with surface being tensed by equi-biaxial tension. The boundary element method (BEM) based on Fast Fourier Transform and conjugate gradient algorithm is extended to deal with this problem. By comparing with existing analytical solutions for the axisymmetric contact between a rigid parabolic indenter and an elastic half space, our numerical simulations are validated having great accuracy. Moreover, the developed BEM algorithm is applied on the calculations of elastic responses of a soft substrate indented by a smooth indenter with general quadric profile and a rough indenter with self-affine fractal surface, respectively. Some essential contact behaviors resulted from the presence of membrane tension are presented and discussed.